A method for calculating semiconductor losses in the matrix converter - Sunter, S; Altun, H (Ieee, 1998)
In this paper, a method for calculating the semiconductor losses in a 3-phase matrix converter is presented. Since there is no any freewheeling path in the matrix converter power circuit and in order to provide safe commutation between the complementary devices, an R-C snubber has been used with each bi-directional switch. Effects of this snubber circuit has been considered in the calculation of the switching losses. The results showing semiconductor losses versus various parameters in the matrix converter have been graphically demonstrated. Hence, the semiconductor losses in the converter can be estimated by examining these results.
9th Mediterranean Electrotechnical Conference (Melecon 98) -- MAY 18-20, 1998 -- TEL AVIV, ISRAEL